Seasonal/Interannual Variation and Controlling Factors for Oxygen and Carbon Isotopes of Ostracod Shells Collected From a Time-Series Sediment Trap in Lake Qinghai - Jin, Zhangdong; Zhang, Fei; Li, Xiangzhong; Wang, Jin; Jin, Chenyu (Frontiers in Earth Science, 2021)
Because the shell substance of an ostracod is derived entirely from the water body where it lives, its chemical compositions are sensitive to aquatic environment and thus have been used to reconstruct past climatic and environmental changes. However, there is controversy about the controlling factors for the different compositions of ostracod shells from various water bodies. In this study, seasonal and interannual variations in daily flux and stable oxygen-carbon isotopic compositions (δl8O, δl3C) for two species of ostracod shells (Limnocythere inopinata and Eucypris mareotica) and their controlling factors are discussed, based on ostracod shell samples collected from a time-series sediment trap from July 2010 through September 2012 and from surface sediments in Lake Qinghai, which were correlated with the state-of-the-art sensing data of the lake water. The results show that the daily flux of L. inopinata shells is an order of magnitude higher than that of E. mareotica. The δ18O and δ13C of both L. inopinata and E. mareotica shells have distinctly interannual and seasonal variations, with species differences. Interannual differences of δ18O for the two species of ostracod shells directly reflect the systematic differences of the summer water temperature between 2010 and 2012. We propose that seasonal variations of both δ18O and δ13C for the two species are controlled by the precipitation of authigenic carbonates induced by high water temperature in summers, highlighting their environmental implications in Lake Qinghai.